The Effectiveness of the 'Stop Pesan Sensi' Program in Reducing Bullying in Indonesian Elementary Schools: A Collaborative Approach Among Teachers, Parents, and Students - Puspitasari, Wiwin; Muhimmah, Hitta Alfi; Nursalim, Mochamad (Journal of Innovation and Research in Primary Education, 2025)
Bullying in elementary schools remains a significant challenge that affects students' psychological well-being and academic performance. This study examines the implementation and effectiveness of the "Stop Pesan Sensi" program at SDN Wonokusumo VI/45, focusing on the collaborative roles of teachers, parents, and students in fostering a safe and inclusive school environment. Utilizing qualitative methods such as observations, interviews, and focus group discussions, this research investigates how active participation from all stakeholders contributes to reducing bullying incidents. Teachers served as facilitators, employing interactive strategies such as storytelling, role-playing, and class discussions to enhance students' understanding of bullying and its consequences. Parents participated in workshops designed to equip them with skills to identify bullying signs and reinforce anti-bullying values at home. Students engaged in creative activities, including drama performances, poster campaigns, and open forums, which promoted empathy and positive behavioral changes. Quantitative data showed a significant decrease in bullying incidents over three months, from 120 cases before the program to 20 cases after. The findings highlight the importance of a holistic and participatory approach in bullying prevention programs. Collaboration among educators, families, and students creates a supportive environment that not only reduces bullying but also fosters tolerance and social-emotional learning. This study recommends expanding such integrated programs across schools to strengthen character development and promote a positive school culture. The results contribute valuable insights into effective strategies for bullying prevention in primary education contexts, particularly within Indonesian schools.